A Translation Analysis Of Noun Phrase In A Million Suns Into Sejuta Matahari By Barokah Ruziati - Damayanti, Tiara (2016)
This research focused on the translation analysis of noun phrase in A Million Suns into Sejuta Matahari by Barokah Ruziati. The objectives of this research are (1) to classify the translation shift of noun phrase in A Million Suns into Sejuta Matahari by Barokah Ruziati and (2) to describe the equivalent of translation of noun phrase in the novel and its translation. This research belongs to descriptive qualitative research. The object of this research is the noun phrases and its translation found in A Million Suns novel translated into Sejuta Matahari by Barokah Ruziati. The data are sentences containing noun phrase and the data source is a novel entitled A Million Suns by Beth Revis which is translated into Sejuta Matahari. The writer uses the documentation and interviewing technique to collect the data. Then, to prove the validity of the data, the writer uses the triangulation where the data sources are from the novel and informant. The data are analyzed by comparing method. The result of this research shows that there are two types of translation shift: level shift and structural shift. First, the level shift occurs in 539 data or 10.1% of noun phrase translation. The level shift is divided into 6 types, there are: NP translated into noun, verb, adverb, adjective, number, and pronoun. Second, there are 4778 data or 89.9% of noun phrase included into the structural shift. The structural shift occurs in the translation of noun phrase into: NPa, NPb, NPc, NPd, NPe, NPf, NPg, NPh, and NPi. The equivalent of noun phrase translation is divided into equivalent and non equivalent translation. The equivalent translation occurs in 5317 data or 100% of data and none of them belongs to non equivalent translation.